Unmentionables: Some Remarks on Taboo - Stefano Predelli (Institute of Philosophy of the Slovak Academy of Sciences, 2021)
This paper discusses the phenomenon of linguistic taboo. It contrasts that phenomenon with the truth-conditional and non-truth-conditional dimensions of meaning, paying particular attention to slurs and coarseness. It then highlights the peculiarities of taboo and its meta-semantic repercussions: taboo is a meaning-related feature that is nevertheless directly associated with the tokening process. In the conclusion, it gestures to the role of taboo within a theory of linguistic action and the standard framework for conversational exchanges. On these results, I am going to end by looking at some of the harms that epistemic injustice inflicts upon its victims.